Effects of close cutting on ground cover and quality of a polystand of Manilagrass and cool season turfgrasses - Grossi, Nicola; Fontanelli, Marco; Frasconi, Christian; Martelloni, Luisa; Raffaelli, Michele; Peruzzi, Andrea; Gaetani, Monica; Magni, Simone; Caturegli, Lisa; Volterrani, Marco; Pirchio, Michel (Italian Journal of Agronomy, 2019)
Warm season turfgrasses can be grown successfully in the transition zone, but dormancy occurs to some extent during the winter. Overseeding with cool-season turfgrasses is necessary if winter dormancy of warm season turfgrasses is not tolerated. The increasing availability of zoysiagrass cultivars has enabled this genus to be considered suitable for low-maintenance golf courses, especially for golf tees and golf fairways. On the other hand, zoysiagrasses have the most rigid leaves of all turfgrass species, followed by bermudagrasses and by the other warm season turf species. Thus, to have a high mowing quality, mowers working constantly on zoysiagrasses require more sharpening than mowers working on other grasses. Rotary mowers are not suitable for mowing at low heights and often result in scalping, while reel mowers perform optimal mowing at a short height (below 2.5 cm) but require accurate management and frequent sharpening. Autonomous mowers have proven to produce a superior turf quality compared with traditional walk-behind rotary mowers, but no autonomous mower has ever been tested at a low mowing height on an overseeded warm season turfgrass. Because of this, the trial was carried out to simulate a golf tee overseeded with cool season turfgrasses, with low input fertilisation rates and with one of the most difficult turf species to mow; i.e. Zoysia matrella (L.) Merr. The trial was carried out in San Piero a Grado (Pisa, Italy) from October 2016 to October 2018. After a two-year period the best turf quality was achieved with Festuca rubra L. ssp. cultivars among the overseeded species, especially during fall. In many cases turf quality increased after manila grass green up since the combination of both cool season and warm season species gave a higher quality to the turfgrass, due to the finer leaf texture and higher shoot density of some cool season species. Moreover, recovery of manila grass ground cover was satisficing. In conclusion, a polystand of manila grass and Festuca rubra ssp. could be suitable for golf tees with low-input management.